Beam-combining superconducting detector for submillimetre-wave astronomical interferometry - Withington, S; Campbell, E; Yassin, G; Tham, C; Wolfe, S; Jacobs, K (2003)
The feasibility of making single-chip, superconducting detectors for submillimetre-wave astronomical inteferometry is demonstrated. An experimental device based on back-to-back corrugated horns, and back-to-back finline transitions, was fabricated. The detector was illuminated at 350 GHz, using a coherent laboratory source, and 0.6° fringes were measured.